The Spanish Civil War : Revolution and Counterrevolution - Bolloten, Burnett (Book collections on Project MUSE., 2015)
This work offers a comprehensive history and analysis of Republican political life during the Spanish Civil War. Completed by Burnett Bolloten just before his death in 1987 and first published in English in 1991, 'The Spanish Civil War' is the culmination of fifty years of dedicated and painstaking research and is the most exhaustive study on the subject in any language.